Zé Correto e a construção dos modos de existência do sujeito em situação de rua - Feltes, Danielle Lasarotto (2017)
This dissertation presents an essay about the life story of a person in street situation in Francisco Beltrão, PR, as well as of the relations that are established between the speeches and the building of processes of subjectivation this person. We use as analytical referential the essays of Michel Foucault, embracing as method the discourse analysis. The discourses are analyzed by means of concepts as Biopolitics and population developed by Foucault, since the same involve in process of formation of the subject and their ways of existence. For this purpose, used it the field research with data collection through technique of interview with a person in street situation called "Zé Correto. These data allowed to discuss the following questions: job, insecurity, religion, social and family relationships and actions of public policies intended the person in street situation. It is emphasized here that these questions contributed to understand the ways of existence of "Zé Correto". In this regard, we check that the constitution of subject in the process of building of themselves and this implies both in the relation with itself and with the relations of power which have the objective of conducting the behaviors that can happen through biopolítical actions that lead the subjects to live within what is considered normal. Get on that the transformations for which "Zé Correto" passed interfere in polítical relations, since, "Zé" will act in building of his interaction with the State and with the services of public policies, causing tensions between institutions/State and the reality of people living on the streets. These tensions result in new ways of subjectivation as well as of control of bodies, building new ways of existence.